2003
DOI: 10.1579/0044-7447-32.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Climate Oscillations and Land-use Changes on Streamflow in the Central Spanish Pyrenees

Abstract: The terms ∆ soil and ∆ snow can be ignored when evaluating big catchments on a yearly basis under a Mediterranean climate with dry summers. It is assumed that the soil and snow water storage are almost completely exhausted by the end of the hydrological year. The term ∆ aquifers can also be neglected when the global water balance is not greatly affected by subterranean circulation. Equation 1 then becomes: R = PET Eq. 2 Thus, the main variables that control water yield in a basin are precipitation, interceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(106 citation statements)
references
References 21 publications
1
100
0
5
Order By: Relevance
“…They attributed these changes to a decline in agricultural and pastoral activities. Begueria et al (2003) reported a negative trend in discharge in the central Pyrenean rivers coinciding with major changes in land management (land was abandoned and progressively covered by dense vegetation). A trend of progressive and intense reduction in run-off was confirmed by other experimental studies in the Pyrenees (Garcìa-Ruiz et al, 1995, 1996Molinillo et al, 1997).…”
Section: F_slp Slopementioning
confidence: 99%
“…They attributed these changes to a decline in agricultural and pastoral activities. Begueria et al (2003) reported a negative trend in discharge in the central Pyrenean rivers coinciding with major changes in land management (land was abandoned and progressively covered by dense vegetation). A trend of progressive and intense reduction in run-off was confirmed by other experimental studies in the Pyrenees (Garcìa-Ruiz et al, 1995, 1996Molinillo et al, 1997).…”
Section: F_slp Slopementioning
confidence: 99%
“…This landscape resulted from strong human pressures in recent centuries, including deforestation, frequent wildfires, overgrazing, and the cultivation of steep slopes; these factors had a particularly strong effect upon the lower and mid-level parts of the mountain (Lasanta et al, 2006). Most of these activities were abandoned during the middle of the twentieth century, resulting in important hydrological and geomorphic changes in the Central Pyrenees (Beguería et al, 2003).…”
Section: Study Areamentioning
confidence: 99%
“…Similar hydrological, geomorphological and ecological consequences have been assessed in other fluvial systems. Such modifications have also been studied on the tributaries of the Ebro (García-Ruiz et al, 2001;Beguería et al, 2003;Batalla, 2003;Batalla et al, 2004;Acín, 2004;Granado, 2004;Frutos et al, 2004;Ollero and Martín-Vide, 2005). Most of the cases studied dealt with transformation of braided channels into meandering ones and problems due to incision, human invasion processes on the riparian corridors, and significant reductions of the channel mobility over the last decades.…”
Section: Introductionmentioning
confidence: 99%